2021
DOI: 10.7759/cureus.17045
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Cholangitis Caused by Methicillin-Resistant Staphylococcus aureus Species in a Patient With Cystic Fibrosis

Abstract: Ascending cholangitis is a bacterial infection of the extra-hepatic biliary system and presents as a life-threatening systemic condition. Increased bacterial loads and biliary obstruction favor bacterial translocation into the vascular and lymphatic systems. Common organisms isolated are Escherichia Coli , Klebsiella , Enterococcus species, and Enterobacter species . Methicillin-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
1
0
0
Order By: Relevance
“…Among the four dominant bacterial communities, the in vivo data suggested that Staphylococcus_xylosus and Staphylococcus_lentus treatment aggravated the liver fibrosis. Interestingly, several studies demonstrated that Staphylococcus was recognized as an important pathogen in patients with chronic liver diseases and was closely related to the occurrence of cystic fibrosis (Obeidat 2021 ; Kang et al 2010 ), which were similar to us and may partly support our data. In fact, the potential mechanisms of resveratrol affecting liver fibrosis are complex.…”
Section: Discussionsupporting
confidence: 89%
“…Among the four dominant bacterial communities, the in vivo data suggested that Staphylococcus_xylosus and Staphylococcus_lentus treatment aggravated the liver fibrosis. Interestingly, several studies demonstrated that Staphylococcus was recognized as an important pathogen in patients with chronic liver diseases and was closely related to the occurrence of cystic fibrosis (Obeidat 2021 ; Kang et al 2010 ), which were similar to us and may partly support our data. In fact, the potential mechanisms of resveratrol affecting liver fibrosis are complex.…”
Section: Discussionsupporting
confidence: 89%